CONTINUOUS PRODUCTION OF PURE SQUALENE BY USING COLUMN CHROMATOGRAPHY - Dosis Undjung (Universitas Gadjah Mada, 2005)
The purpose of this research was to produce pure Squalene using the Chromatography Column of Continuous System, so that it will be applicable in home industry. The raw material was a Shark caught from the sea water in Katingan Regency, Central Kalimantan. The result of this research concludes that the Column Chromatography of Continuous System in the experiment was able to produce pure Squalene with the level of purification of 79.89 % out of raw material was as long 180 minutes, by the elution speed of 4 mL per minute, and the eluen (liquid of the raw material) needed was as much as 900 mL, the solution lost (2 % of dietil eter in benzene) during the process was 2.04 %, the temperature in the heater tube was 110 oC, the number of the Silica gel G 40 types as what so-called solid phase in this process to purify 90 g of raw material was 90 g, and the amount of the solution remained in the pure Squalene was 1.5 ppm. Column Chromatography of Continuous System may be applicable in home industry to produce pure Squalene from Shark Liver Oil, the materials and equipment for this activity can be easily found as they are available in markets. A further analysis is needed to find out of contained compound for its further use.